Global Citizenship in the Era of Disruption: Preparing Critical, Inclusive, and Responsible Global Citizens - Kartika, Rika; Ibrahim, Intan Maharani; Pudjiastuti, Sri Rahayu (Universitas Negeri Surabaya, 2025)
The era of disruption, characterized by rapid technological advancement, globalization, and complex transnational challenges, has significantly transformed the concept and practice of citizenship. This article aims to examine the role of Global Citizenship Education (GCE) in preparing critical, inclusive, and responsible global citizens. Employing a qualitative conceptual approach based on a systematic review of relevant literature, this study synthesizes theoretical frameworks and empirical findings related to global citizenship and civic education. The findings indicate that global citizenship extends beyond national boundaries and encompasses global awareness, intercultural inclusivity, ethical responsibility, and active civic participation. In the context of disruptive global change, education plays a strategic role in integrating global perspectives with local values to foster democratic attitudes and social responsibility. The novelty of this article lies in positioning global citizenship as a transformative paradigm within civic education that responds to global crises while strengthening moral and democratic values. The study concludes that the systematic integration of GCE is essential for developing citizens capable of navigating global complexity in a responsible and ethical manner.